PRIORITY MUNICIPALITIES FOR DISASTER RISK MANAGEMENT: A CONTRIBUTION TO THE DECISIONMAKING PROCESS - Barrenechea-Riveros, Fabiola (Revista Geográfica de América Central., 2016)
In case of a disaster, local governments are the first to help his community. However, they do not always have adequate resources to develop efforts aimed at preventing and responding to disastrous events. Thus, 25 priority municipalities for Disaster Risk Management, according to physical, social, and economic variables, considering the most common events that cause impacts in the population were identified. This prioritization will guide the efforts made by public services in the areas of disaster risk reduction, in order to execute effective, efficient, and timely actions.